Pediatric Acute Respiratory Distress Syndrome in Pediatric Allogeneic Hematopoietic Stem Cell Transplants: A Multicenter Study*. Issue 4 (April 2017) - Rowan, Courtney M.; Smith, Lincoln S.; Loomis, Ashley; McArthur, Jennifer; Gertz, Shira J.; Fitzgerald, Julie C.; Nitu, Mara E.; Moser, Elizabeth A. S.; Hsing, Deyin D.; Duncan, Christine N.; Mahadeo, Kris M.; Moffet, Jerelyn; et al.
Abstract : Objective: Immunodeficiency is both a preexisting condition and a risk factor for mortality in pediatric acute respiratory distress syndrome. We describe a series of pediatric allogeneic hematopoietic stem cell transplant patients with pediatric acute respiratory distress syndrome based on the recent Pediatric Acute Lung Injury Consensus Conference guidelines with the objective to better define survival of this population. Design: Secondary analysis of a retrospective database. Setting: Twelve U.S. pediatric centers. Patients: Pediatric allogeneic hematopoietic stem cell transplant recipients requiring mechanical ventilation. Interventions: None. Measurements and Main Results: During the first week of mechanical ventilation, patients were categorized as: no pediatric acute respiratory distress syndrome or mild, moderate, or severe pediatric acute respiratory distress syndrome based on oxygenation index or oxygen saturation index. Univariable logistic regression evaluated the association between pediatric acute respiratory distress syndrome and PICU mortality. A total of 91.5% of the 211 patients met criteria for pediatric acute respiratory distress syndrome using the Pediatric Acute Lung Injury Consensus Conference definition: 61.1% were severe, 27.5% moderate, and 11.4% mild. Overall survival was 39.3%. Survival decreased with worsening pediatric acute respiratory distress syndrome: no pediatric acute respiratory distress syndrome 66.7%, mild 63.6%, odds ratio = 1.1 (95% CI, 0.3–4.2; p = 0.84), moderate 52.8%, odds ratio = 1.8 (95% CI, 0.6–5.5; p = 0.31), and severe 24.6%, odds ratio = 6.1 (95% CI, 2.1–17.8; p < 0.001). Nonsurvivors were more likely to have multiple consecutive days at moderate and severe pediatric acute respiratory distress syndrome ( p < 0.001). Moderate and severe patients had longer PICU length of stay ( p = 0.01) and longer mechanical ventilation course ( p = 0.02) when compared with those with mild or no pediatric acute respiratory distress syndrome. Nonsurvivors had a higher median maximum oxygenation index than survivors at 28.6 (interquartile range, 15.5–49.9) versus 15.0 (interquartile range, 8.4–29.6) ( p < 0.0001). Conclusion: In this multicenter cohort, the majority of pediatric allogeneic hematopoietic stem cell transplant patients with respiratory failure met oxygenation criteria for pediatric acute respiratory distress syndrome based on the Pediatric Acute Lung Injury Consensus Conference definition within the first week of invasive mechanical ventilation. Length of invasive mechanical ventilation, length of PICU stay, and mortality increased as the severity of pediatric acute respiratory distress syndrome worsened.